EXPLOITATION OF INFECTIVITY POTENTIAL OF CpCDV A GEMINIVIRUS AGAINST DIFFERENT FRUIT CROPS AND WILD HOST PLANTS - ATIF, M; AHMAD, F; MANZOOR, MT; GILANI, K; ALI, Q; SARWAR, M; ANJUM, S; ALAM, MW; HUSSAIN, A (Biological and Clinical Sciences Research Journal, 2022)
The Chickpea Chlorotic Dwarf Virus (CpCDV) has been found very much destructive not only for the chickpea crop but also for lentils, cotton, papaya and other wild hosts. During past few years, it has been found that the mastrevirus caused adverse effects on the hosts and caused to reduce crop plant yield up to 95%. This virus has been found as a most prevalence in the dry regions with an equally important pathogen in other parts of the world especially in American and European countries. The capability has been reported due to the rapid changes in viral genome. Vector species also played an important role in the spread of this virus. Here the evolutionary study of about 244 genomes was performed. All genomes obtained from food, fiber and wild plants. Genomes obtained from wild plants are ancestors and rest has been found as the offsprings. According to our finding, the CpCDV has been found an important pathogen not only for Fabaceae family but also for Malvaceae, Solanaceae, Cucurbitaceae and many more.